Flexural Behaviour of Reinforced Concrete Beams using Alkali Activated Binders - Paswan, Rajesh Kumar; Kumar, Virendra; U. Kapure, Gajanan; Murthy, Y. Rama (International Journal of Sustainable Construction Engineering and Technology, 2023)
This article discusses several different percentages of alkali activators that can be used in place of conventional cement with ground granulated blast furnace slag (GGBFS) resulting in alkali activated binder (AAB). They are labelled as G10 percent, G7 percent, G6 percent, and G5 percent, respectively, since they include 90 percent, 93 percent, 94 percent, and 95 percent of GGBFS, as well as 10 percent, 7 percent, 6 percent, and 5 percent alkali as an activator, respectively. A comparison of specimens formed of reinforced beams utilising alkaline binders and conventional cement is shown in this study. One of the six varieties of reinforced concrete beams is composed of Portland slag cement, four of the beams are cast with varied chemical concentrations of AAB concrete, and the last beam is produced with Ordinary Portland cement. They are examined using four-point bend test. The behaviour of reinforced concrete beams composed of AAB and conventional cement is analysed in this study, and the crack types and ultimate loads of failure are also demonstrated. It was established that the combination of alkali activated binders known as G10 percent was the most successful one since it led to good performance when compared to the OPC concrete.